Rat cultured neuronal and glial cells respond differently to toxicity of unconjugated bilirubin - Silva, RFM (2015)
High levels of unconjugated bilirubin (UCB) can be neurotoxic. Nevertheless, the mechanism of UCB interaction with neural cells is still unknown. This study investigates whether cultured rat neurons and astrocytes respond differently to UCB exposure. UCB